TPACK (TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE) GURU DALAM PEMBELAJARAN YANG DAPAT MENGAKOMODASI KETERAMPILAN ABAD 21 - Handi Suganda, - (2020)
This study aims to describe the ability of TPACK biology teachers in learning that can accommodate the demands of 21st-century skills. The research method used is descriptive research. Research participants were taken used a convenience sampling technique. The participants in this study amounted to five teachers with a range of different material consisting of teachers who taught classes X, XI, and XII. Biology teacher TPACK was identified based on CoRes, RPPs, and Pap-eRs which were supported by questionnaire perception and consideration of 21st-century learning. The results showed that TPACK biology teacher in accommodating 21st-century skills before learning in growing category of 20% and 80% were in the pre category TPACK. After the learning reflection process, 40% of teachers are in growing category and 60% of teachers are in the pre-TPACK category. The results of the conformity assessment of CoRes with RPP before learning had a percentage score of 53.34% and after learning amounted to 71.11%. In general, teachers already have perceptions and considerations of learning that have been very good. Teachers need advanced learning training especially on aspects of learning technology in teachers with a teaching experience span of more than 10 years.